#TITLE_ALTERNATIVE# - ODE AWALIAH (NIM : 22315015), WA
Sulawesi Island has a complex tectonic setting. This is closely related to the position of the island of Sulawesi which is located in the active collision of three plates of the world, the Pacific Ocean Plate that relatively moving to the west, the Australia-Indies Plate that relatively moving to the north, and the Eurasian Continental Plate that relatively not moving. Some results of the geological manifestations, such as fault systems, volcano zones, diverse lithologic conditions, and unique Sulawesi geometry that resembles the letter 'K', illustrate that the tectonic processes that make up the island are interesting to be inspected. Based on these conditions, the authors are interested to identify the subsurface structure of Sulawesi Island and its surroundings by applying Ambient Noise Tomography (ANT) method. In this research, daily data of seismic data of BMKG and GSN network are used. These data are from 21 pieces from scattered data in Sulawesi Island in the span of six months (from 1st July to 31th December 2016). In the data processing phase, the Green empirical function is calculated through a cross-correlation process on each pair of two station data. The characteristics of the Green function are associated with the structure of the subsurface seismic velocity, making it possible to be used as input data in subsurface modeling. From this research, it is obtained the structure of shear wave velocity (Vs) 3-D in the southern of Sulawesi, North Sulawesi, and the Gorontalo Basin. In the South Sulawesi Arm obtained sub-surface structures for a depth of 2 - 30 km, while the North Sulawesi Arms and Gorontalo Basin are in the range of 2 - 40 km depth. From the tomogram, it is obtained the identified several geological structures such as basin, fracture, volcano zone, anticline, and also estimate the depth of moho. The structure of the basin is in the area around the Gorontalo Basin. Tomogram also succeeded in indicating the presence of thick sediment indication in the Southwest-Northeast Gorontalo Basin. An anticline-like structure is found in the area around Dolang and Ampana which associated with low-velocity structures and currently petroleum exploration has been undertaken. The volcano zone on Una - Una Island (Gunung Colo) is associated with high velocity structures. Wallanae fractures and Gorontalo fractures are clearly identified on the tomogram represented by the boundary between velocity contrast and North West-South-oriented orientation. In the South Arm, it is estimated that the moho is at a depth of 20 -30 km, the North Arm is estimated to start at a depth of 20 km, in the Gorontalo Basin estimated to be at a depth of 20 - 30 km.